2021
DOI: 10.1111/tri.13990
|View full text |Cite
|
Sign up to set email alerts
|

Development of ex situ normothermic reperfusion as an innovative method to assess pancreases after preservation

Abstract: Summary Static cold storage (SCS) is the standard method for pancreas preservation prior to transplantation; however, it does not permit organ assessment. Normothermic reperfusion (NR) is utilized clinically for other organs to assess viability. Our aim was to develop NR using normothermic machine perfusion technique to simulate reperfusion at the time of transplantation, enabling evaluation of oxygenated hypothermic machine perfusion (HMPO2) as a newer strategy to optimize pancreas preservation. 13 porcine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, we have refined this method of retrieval over a number of years and previously described the strengths and limitations ( 50 ). We have shown acceptable reproducibility in preclinical dose–response studies where kidneys underwent normothermic perfusion as a basis for a clinical trial ( 17 ) and have also demonstrated that this method of multiple organ procurement is adequate for comparing different preservation methods in pig pancreases ( 51 ). We have not included histological evaluation in this study due to findings from a previous work on slaughterhouse pig kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have refined this method of retrieval over a number of years and previously described the strengths and limitations ( 50 ). We have shown acceptable reproducibility in preclinical dose–response studies where kidneys underwent normothermic perfusion as a basis for a clinical trial ( 17 ) and have also demonstrated that this method of multiple organ procurement is adequate for comparing different preservation methods in pig pancreases ( 51 ). We have not included histological evaluation in this study due to findings from a previous work on slaughterhouse pig kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Authors often claim to use an oxygenated perfusate with however no further details on oxygenator type or size and the lack of perfusate oxygen partial pressures (Table 1). Only two recent studies present perfusate oxygen levels [41,59]. Lemkuil et al from the UK have demonstrated the perfusate oxygen-dependent ATP-reloading of the pancreas, similar as seen with other solid organs.…”
Section: How Much Perfusate Oxygen Is Beneficial During Hypothermic P...mentioning
confidence: 85%
“…They reported noninferiority of the latter compared with CS in terms of survival and endocrine and exocrine graft function. Another experimental model by Ogbemudia et al 23 in 2021 compared the outcome of hypothermic oxygenated machine perfusion versus CS for 6 h by subjecting the grafts to 1 h of normothermic regional perfusion for reperfusion after ischemia. They reported better perfusion characteristics, decreased macroscopic edema, and normal macroscopic appearance compared with CS during reperfusion, suggesting a role of ex situ machine perfusion in alleviating tissue injuries associated with cold ischemia.…”
Section: Discussionmentioning
confidence: 99%